Puerperal women's perceptions of obstetric violence during labor - Santos, Vanessa de Melo; Westphal, Flavia; Rocha, Chayene Aguiar; Fernandes, Hugo; Souza, Fabiana de; Goldman, Rosely Erlach (ABCS Health Sciences, 2023)
Introduction: When perceptions from healthcare users regarding the services offered by health institutions are taken into account, they become a tool to improve the quality of healthcare actions. Objective: To understand the perception of puerperal women about obstetric violence during labor. Methods: A descriptive mixed-methods study was carried out in a maternity hospital in the city of São Paulo with 31 postpartum women from August to November 2020. Quantitative data were collected in the first step, followed by the collection and analysis of qualitative data based on the theoretical framework of social representations and content analysis to decompose the interview material. Results: Two categories were identified from the perspective of the obstetric violence perception, physical abuse, and abandonment during health care. From the perceptions of puerperal women concerning obstetric violence during labor, it was possible to identify that 11 women have experienced it. Of these, 7 did not initially mention violence, but when questioned, they indicated the occurrence of inappropriate or unnecessary practices that fit the obstetric violence definition, and 20 claimed not to have experienced violence. Conclusion: It was evidenced that women sometimes did not recognize that they experienced obstetric violence, and some of those women who did had received inadequate information. There is an urgent need to reflect on the current scenario of childbirth care, reformulation of care practices, and professional awareness of good practices and evidence-based medicine.